A Feasibility Study on the Establishment of a Leather Tannery - Casabar, Mayumi B.; Ferrer, Christine Joy.; Santos, Almira C. (Diliman, Quezon City College of Engineering, 1994)
MARKET STUDY- After first identifying upper leather, the leather needed to be produced by the proposed tannery, its quality and uses. The group examined the industry that presently supplies the product. This includes a description of the present state of the industry, its problems (poor quality of rawhides, lack of technology know-how, competition from imported leather) and the other factors that affect the quality and availability of the leather. It is followed by the definition of the target market. It is presented by identifying two cases: 1) when only OTTO shoes is being considered and 2) when the market of other leather users are included. The target market which is OTTO shoes for both cases is further described. The competition for the proposed tannery is then evaluated for OTTO shoes and then for the whole industry while taking note of the effect of the prices of substitute and similar products. A price study led us to determine the upward trend of prices and to suggest that the product be priced at cost when catering to OTTO only, and at industry price if outside market is considered. The most important part of the study is the demand analysis wherein the demand of the whole industry, and OTTO specifically, is described. The qualitative analysis where the future demand is estimated using various projection methods and limited data is supplemented by the qualitative analysis naming the factors that contribute to the demand?s behavior and growth. A comparison between the projected industry supply and the industry of leather is made in the supply-demand analysis showing that for case 2, there is a share of the market to be supplied. Finally, the market strategy is detailed on the last part, which suggests how to attack the market problem through the 4 P?s. TECHNICAL STUDY- The manufacturing selected by the group was the common manufacturing process among the tanneries visited and even similar to the one discussed in the books and references read. The projected leather demand of OTTO shoes was used to determine the annual and daily production schedule of the tannery. The group used the daily production schedule to determine the number and type of machines and the labor requirement of the tannery. A total of 14 types of machines will be purchased for the tannery, most will be imported making deals directly with contacts abroad or through dealers. On the first year of operation, or at 33.33% capacity, the operating time of the tannery will be 15 days. There were two general sites considered for the location of the tannery: Bulacan and Marikina. There are limited available areas in Bulacan and there is a greater chance of renting than building a tannery. Since there are facilities needed for the manufacturing process that are not available in existing tanneries, building a tannery on bought land is preferred. The total required area for the warehouse-type building, waste disposal area plus parking space is 5,402.16 sq. m. Quite a large area was allotted for waste disposal area, since the tannery being a high pollutant plant require4s space to treat or allow its solid waste to settle and form as sludge and its liquid effluent to be oxidized so that when released, it will not pollute the surrounding areas. In the end, after making a rough summary of costs for initial operation, putting up a tannery turned out to be capital intensive. The cost raw materials required, rawhides and chemicals plus the cost of purchasing the machines and the land make up most of the cost including the building cost. FINANCIAL STUDY- The total project cost was finalized, while taking note of the assumptions taken while using each cost item in the preparation of pro-forma statements. In the income statement for the leather tannery, the project will have a negative net income for the second year because the first was considered a grace period. In the succeeding years, the income will grow, the assets will grow, and the liabilities will decrease as payments for the loan are being done for each year. Improving with them are the financial ratios taken for all the years being considered. The sources of financing is from the owner and a bank, particularly Metrobank, the one they have an account on. The project cost (a total of P 36,500,000) is thus divided in the following percentages: 10% will be provided by the project proponent: OTTO or S.O.G. Mfg. Corp.: and 90% will be loaned from the bank at 16% per annum, to be paid in six years (equal to the number of years under study). The project was thus concluded as feasible under the given conditions assumed and assuming again that creditors approve the establishment of this leather tannery.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Dyes and dyeing--Leather.; Leather goods; Participatory monitoring and evaluation (Project management)